2000
DOI: 10.1097/00005392-200004000-00083
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Structure and Function of the Rabbit Urinary Bladder Following Partial Outlet Obstruction

Abstract: Prolonged partial bladder outflow obstruction is accompanied by a progressive decrease in contractility of SM. The present study describes the structural damage that occurs in the bladder wall in response to partial outlet obstruction and correlates these observations with the contractile dysfunction with which it is associated. Furthermore, mitochondrial damage in vessels and fibroblasts is suggestive of bladder wall ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 23 publications
2
54
0
3
Order By: Relevance
“…4 Chronic partial bladder outlet obstruction causes bladder ischemia leading to a progressive decrease in detrusor contractility. 5,6 According to previous reports, clinical causes, including insufficient blood supply (ie, arteriosclerosis) and bladder outlet obstruction (ie, BPH), induce ischemia and the ischemia/reperfusion cycle is accompanied by micturition and neurogenic and/or myogenic contractile dysfunction. 7 Diabetes impairs vascular endothelial function due to nitric oxide (NO) hyposecretion and causes atherosclerosis, resulting in reduced blood supply.…”
Section: Introductionmentioning
confidence: 99%
“…4 Chronic partial bladder outlet obstruction causes bladder ischemia leading to a progressive decrease in detrusor contractility. 5,6 According to previous reports, clinical causes, including insufficient blood supply (ie, arteriosclerosis) and bladder outlet obstruction (ie, BPH), induce ischemia and the ischemia/reperfusion cycle is accompanied by micturition and neurogenic and/or myogenic contractile dysfunction. 7 Diabetes impairs vascular endothelial function due to nitric oxide (NO) hyposecretion and causes atherosclerosis, resulting in reduced blood supply.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has demonstrated that ischemia followed by reperfusion are major etiological factors in obstructive bladder dysfunction (3,4). Specifically, blood flow to the bladder's smooth muscle and mucosa decrease with obstructive Basic and Translational Urology doi: 10.1590/S1677-55382010000600014 dysfunction resulting in tissue hypoxia, increased free radical generation, decreased contraction, denervation, and mitochondrial dysfunction (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…From our studies on partial outlet obstruction and bilateral ischemia, we have shown that mitochondria are one of the most sensitive sub-cellular organelles to develop oxidative stress and free radical damage (3,4,(24)(25)(26)(27). We use citrate synthase as a marker enzyme for mitochondrial function (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies of the relationship between bladder dysfunction and blood flow [1,2], with a heterogeneous distribution of blood flow in the bladder, and large differences in blood flow between the muscular and mucosal layers reported [3][4][5][6]. The relationship between bladder dysfunction and blood flow has also been recognised.…”
Section: Introductionmentioning
confidence: 99%